Are exchange rates really free from seasonality? An exploratory analysis on monthly time series - Roberto Cellini; Tiziana Cuccia (The Open Economics Journal, 2011)
This study deals with the seasonality of monthly time series of nominal exchange rates. Available literature overlooks seasonality in nominal bilateral exchange rates, and generally assumes that such rates are non-seasonal. We show that seasonality is absent in recent data, while it was present in selected cases from the Seventies and Eighties of the past century. We suggest that these pieces of evidence are consistent with the general equilibrium models of exchange rate determination.
Keywords: C22; F31; 330; seasonality; exchange rates